2002
DOI: 10.1079/bjn2002720
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate fractions of legumes: uses in human nutrition and potential for health

Abstract: Starch and fibre can be extracted, using wet or dry processes, from a variety of grain legumes and used as ingredients for food. a-Galactosides can be isolated during wet processes from the soluble extract. Starch isolates or concentrates are mostly produced from peas, whereas dietary fibre fractions from peas and soyabean are commercially available. The physico-chemical characteristics of fibre fractions very much depend on their origin, outer fibres being very cellulosic whereas inner fibres contain a majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
206
1
10

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(229 citation statements)
references
References 76 publications
12
206
1
10
Order By: Relevance
“…The starch content of chickpea and wheat flours are 51 % and 64 %, respectively (Idriss et al 2012). The higher percentage of amylose (30-40 %) in chickpea starch compared to the 20 % in wheat starch (Guillon and Champ 2002) makes chickpea starch more resistant to digestion (Muir and O'Dea 1992). The fiber content of chickpeas is 16.4 % (Berrios et al 2010) versus 12.2 % in whole-wheat flour and 3 % in white flour (Idriss et al 2012) and the protein content of raw chickpea flour was reported as 25.5 % compared to 11.9 % in wheat flour (Idriss et al 2012).…”
Section: Introductionmentioning
confidence: 94%
“…The starch content of chickpea and wheat flours are 51 % and 64 %, respectively (Idriss et al 2012). The higher percentage of amylose (30-40 %) in chickpea starch compared to the 20 % in wheat starch (Guillon and Champ 2002) makes chickpea starch more resistant to digestion (Muir and O'Dea 1992). The fiber content of chickpeas is 16.4 % (Berrios et al 2010) versus 12.2 % in whole-wheat flour and 3 % in white flour (Idriss et al 2012) and the protein content of raw chickpea flour was reported as 25.5 % compared to 11.9 % in wheat flour (Idriss et al 2012).…”
Section: Introductionmentioning
confidence: 94%
“…Nevertheless, lupin is currently receiving international interest as an alternative source of food ingredients for the future. The dietary fibre content of ASL kernels is higher than that of most other legumes, making up around 40% of the kernel weight (Johnson & Gray, 1993;Petterson, 1998;Guillon & Champ, 2002). LKFibre has been shown to have potential in the manufacturing of palatable fibre-enriched products such as baked goods and pasta (Clark & Johnson, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies show that yellow pea protein intake was associated with reduced blood glucose and subsequent food intake (2,36), whereas the intake of pea hull fiber resulted in increased bowel movement frequency in elderly individuals (10) and when combined with inulin reduced energy intake and improved stool frequency in constipated children (15). Pulse fractions include resistant starch and galactooligosaccharides such as raffinose, stachyose, and verbascose (17,25), which provide benefits such as blood glucose control and improved gastrointestinal function.…”
mentioning
confidence: 99%